2015
DOI: 10.1002/2014ja020822
|View full text |Cite
|
Sign up to set email alerts
|

On the onset of ionospheric precursors 40 min before strong earthquakes

Abstract: Heki (2011) and Heki and Enomoto (2013) claimed that anomalous, yet similar, increases of ionospheric total electron content (TEC) started~40 min prior to the 2011 Tohoku-Oki, as well as before other M w > 8 earthquakes. The authors concluded that the reported TEC anomalies were likely related to the pending earthquakes, suggesting also that TEC monitoring may be useful for future earthquake prediction. Here we carefully examine the findings of Heki (2011) and Heki and Enomoto (2013) by performing new analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 55 publications
2
51
0
Order By: Relevance
“…If we assume that ULF magnetic seismogenic signals actually appear before earthquakes, there is no physical reason that the P anomalies must show periodicity in a restricted time range (e.g., 11–15 days) before the main shock. This hypothesis is highly questionable since earthquakes occurred in an area having a radius of 100 km were generated by different fault zones, and thus, it is unlikely that they might share similar precursory phases [see Masci et al ., ]. Still, what is the physical mechanism that would generate electromagnetic signals just a few days before the earthquake?…”
Section: The Statistical Analysis By Han Et Al []mentioning
confidence: 99%
See 2 more Smart Citations
“…If we assume that ULF magnetic seismogenic signals actually appear before earthquakes, there is no physical reason that the P anomalies must show periodicity in a restricted time range (e.g., 11–15 days) before the main shock. This hypothesis is highly questionable since earthquakes occurred in an area having a radius of 100 km were generated by different fault zones, and thus, it is unlikely that they might share similar precursory phases [see Masci et al ., ]. Still, what is the physical mechanism that would generate electromagnetic signals just a few days before the earthquake?…”
Section: The Statistical Analysis By Han Et Al []mentioning
confidence: 99%
“…Journal of Geophysical Research: Space Physics 10.1002/2015JA021336 main shock. This hypothesis is highly questionable since earthquakes occurred in an area having a radius of 100 km were generated by different fault zones, and thus, it is unlikely that they might share similar precursory phases [see Masci et al, 2015]. Still, what is the physical mechanism that would generate electromagnetic signals just a few days before the earthquake?…”
Section: Superposed Epoch Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from these coseismic disturbances, Heki [] found ionospheric electron enhancements starting ~40 min before the 2011 Tohoku‐oki earthquake ( M w 9.0), Japan, using a dense array of continuous GPS stations. Through debates between critical papers [ Kamogawa and Kakinami , ; Utada and Shimizu , ; Masci et al ., ] and replies to them [ Heki and Enomoto , , , ], Heki and Enomoto [] showed that the enhancements preceded eight past earthquakes with M w 8.2 or more. They found that the enhancements started about 20/40 min prior to M w 8/9 earthquakes and that the changes in vertical TEC (VTEC) rates depend on M w as well as background absolute VTEC.…”
Section: Introductionmentioning
confidence: 99%
“…The ionosphere reacts to geomagnetic effect, solar activity, diurnal and seasonal effects, and earthquake, and these factors cause irregularities in the ionosphere (Namgaladze et al, 2012;Li and Parrot, 2018).…”
Section: Introductionmentioning
confidence: 99%